Donor-derived transplant acceptance-inducing cells in composite tissue allotransplantation - Radu, Christian Andreas; Horn, Dominik; Kiefer, Jurij; Gebhard, Martha-Maria; Ryssel, Henning; Köllensperger, Eva; Germann, Günter; Kremer, Thomas (Journal of plastic, reconstructive & aesthetic surgery, 2012)
Background: Composite tissue allotransplantation (CTA) is a newly emerging field of transplantation. Immunological research in CTA has been intensified due to the recent clinical success of hand and face transplantation. Establishing immunological tolerance by adoptive transfer of ex vivo cultured tolerance-inducing cell types is of growing interest. Transplant acceptance-inducing cells (TAICs) are a type of deactivated immunoregulatory macrophages. Methods: A total of 36 allogeneic hind limb transplantations in the rat were performed in six groups. Group A (Lewis (LW) → Brown-Norway (BN)) received Lewis-donor-derived TAICs locally (i.m.). Group B (LW → BN) received Lewis-donor-derived TAICs systemically (i.v.) and group C (Sprague Dawley (Sp-D) → BN) served as a control group receiving Lewis-donor-derived TAICs systemically (i.v.). Groups D (LW → BN), E (LW → BN), and F (BN → BN) also served as control groups with group D receiving no immunosuppression, group E receiving FK506 and prednisolone and group F receiving no immunosuppression with isograft transplantations (BN → BN). The timing of rejection was assessed by clinical observation and histological findings. Results: Rejection of the allogeneic hind limb occurred on average 7.7 days after transplantation in group A and 7.4 days in group B. Rejection was significantly delayed (Log-rank test, p < 0.01) compared to groups C and D, where rejection of the allogeneic hind limb occurred on average 5.8 days and 5.6 days after transplantation. No rejection was seen in groups E and F. Conclusion: For the first time, TAICs have been applied in a CTA model and demonstrated a significant immunosuppressive effect. Even though the immunomodulatory effect is relatively modest, the results of this study justify subsequent research on TAIC therapy to improve experimental and clinical outcome after CTA.
Gesehen am 26.11.2018